Effective Exchange Rate Regimes and Inflation - Philipp Harms; Jakub Knaze (ZBW - Leibniz Information Centre for Economics, 2021)
This paper introduces a new effective exchange rate regime classification. Traditional classifications define the stability or flexibility of a currency with respect to one ("anchor") currency, thus implicitly neglecting information on exchange rate relationships against other currencies. Our new measure is computed as a trade-weighted average of bilateral exchange rate regimes, thus taking into account both direct and indirect relationships against all other currencies. We argue that our "effective" approach is superior when it comes to assessing the impact of exchange rate regimes on inflation, because fixing an exchange rate vis-'a-vis one currency does not completely anchor domestic prices in a world with multiple trading partners. Using our measure of effective exchange rate regimes in a standard empirical analysis of inflation determinants, we find that - compared to freely floating regimes - not only hard pegs, but also narrow and wide soft pegs are associated with significantly lower inflation rates. This challenges the established view that soft pegs do not matter - or are even detrimental - for price stability. We find that the effect of fixing the exchange rate goes significantly beyond the "disciplining effect" on money growth, with the inflation reduction being at least as strong as the effect of an official inflation target.
Keywords: E31; E52; F41; 330; Exchange rate regimes; Effective exchange rates; Inflation